Examination of the linguocultural characteristics of english based on the analysis of american situational comedies - Sokolova, Natalia Leonidovna; Sergeeva, Marina Georgiyevna (Universidade Estadual Paulista, 2021)
The article is devoted to the problem of studying the linguocultural characteristics of English based on the analysis of American situational comedies. The study highlights the role of humor and understanding of the cultural figures, necessary for the most effective English language learning. Summing up the results of the research, situational comedy (sitcom) is the most convenient material for studying the linguocultural characteristics of English, due to the abundance of various linguocultural markers and lexical units. The study aims at improving students’ language proficiency by studying the linguocultural characteristics of English based on the analysis of American situational comedies. The results of the study allow concluding that studying the linguocultural characteristics of English based on the analysis of American situational comedies leads to the improvement of students' language proficiency.